Pengaruh Digital Marketing Bighit Entertainment(Bts) dan minat Pembelian Album/ Merchandise Terhadap Keputusan Daya Beli Fans( Studi Kasus Pada E-Commerce Weverse ) - Suyono Suyono; Sofiani Afifah Hariyanto (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to identify the influence of digital marketing BigHit Entertainment, a kpop agency in the digital era, especially in Indonesia. Research on digital marketing strategies and album sales of the current K-pop group, namely BTS, as well as before and the purchasing power of fans. Quantitative research uses data in the form of articles, videos, and questionnaire data. The strategy carried out by BigHit is in line with the marketing steps of the 4.0 era which began with an understanding of consumer behavior, human-oriented marketing for brand appeal, content marketing for brand recognition. In the process of this strategy, fans mostly consist of young people and women, teenagers play a major role as good promoters and distributors.